The Death Literacy Index: translation, cultural adaptation, and validation of the Chinese version - Che, Sok Leng; Li, Xiang; Zhu, Mingxia; Ng, Wai I (Frontiers in Public Health, 2023)
Objective: Applying public health approaches to address palliative care allows a broader perspective to be gained. The Death Literacy Index (DLI) is a novel instrument designed to assess the knowledge and skills required to access, comprehend, and make informed decisions regarding end-of-life care. By translating the DLI could strengthen the capacity of building a desirable services and policy regarding dying and death. It could also help identifying the barriers of death services and future advocacy efforts. Methods: The DLI was forward translated into Chinese and backward translated through two panels. Two rounds of cognitive interviews and a pilot test (n=53) were conducted before the survey. A sample of 3221 participants was recruited via an online survey in five cities in southern China (Guangzhou, Zhuhai, Jiangmen, Hong Kong and Macao) to evaluate the factor structure, validity and reliability of the translated DLI. Additionally, multi-group confirmatory factor analyses (MGCFA) were also performed to examine measurement invariance across gender and experience of parent(s)’ death. Results: Explanatory factor analysis showed a six-factor structure for the translated DLI, confirmatory factor analysis confirmed the structure. The overall scale and subscales had high internal consistency and satisfactory validity. Results from MGCFA showed that death literacy in different gender and experience of parent(s)’ death to be adequately invariant. Conclusions: The Chinese DLI demonstrated to be a reliable and valid instrument for measuring death literacy among people of southern China, and therefore, can be used both for research and community practice.